Augmented Reality Media Design for Electro-Pneumatic Practical Learning for Vocational High School Students (VHS) - Moch Sukardjo; Uswatun Khasanah; Stephanus Turibius Rahmat; Khaerudin (Universitas Pendidikan Ganesha, 2023)
Many students still need to be skilled and able to practice electro-pneumatic expertise. This research aims to design augmented reality media for electro-pneumatic subjects. This study uses the development research method by adopting the ADDIE model with 5 stages. The media produced in this study will be analyzed for its practicality. The sample in this study was 16 students of class X. The instrument used for experts was using a questionnaire with 4 options. The instrument given to students to find out practicality is in the form of a questionnaire with 2 yes and no options. Data collection techniques using documentation, interviews, questionnaires, and literature review. Data analysis used quantitative descriptive data analysis techniques. The study's results, namely the assessment of instructional design experts from two experts, obtained a score of 4.43. the assessment of two material experts obtained a score of 4.5, and the assessment of two media experts obtained a score of 4.22. It was concluded that augmented reality media designed for electro-pneumatic subjects is feasible. The results of the questionnaire filled out by students scored above 80. From the results of the practicality test, it can be concluded that augmented reality media is quite practical. The implications of applying augmented reality media in practical electro-pneumatic learning in schools will be able to improve students' practical skills.